Physiological and Behavioral Adjustments Relative to Catecholamine Levels During Nesting in Olive Ridley (Lepidochelys Olivacea) and Hawksbill (Eretmochelys Imbricata) Sea Turtles in Masirah Island, Oman. - A.Y.A AlKindi; I.Y. Mahmoud; Fatma Al-Siyabi (Sultan Qaboos University Journal for Science, 2003)
Plasma adrenaline (ADR) and noradrenaline (NA) levels were measured for the first time in natural populations of hawksbill (Eretmochelys imbricata) and olive ridley (Lipedochelys olivacea) in Masirah Island, Arabian Sea; one of the few protected nesting grounds remaining in the world for these two endangered species. Plasma ADR and NA levels were assessed in individuals after they oviposited eggs and completed nesting exercises, and in individuals which were still searching for suitable nesting sites. Blood samples were taken from the cervical sinuses from two groups (oviposited and non-oviposited), which spent at least 1.5 h on the nesting grounds. The duration of the nesting period varied between 1.5 and 2.0 h for both species. There was no significant difference between oviposited and non-oviposited turtles in both species. As the turtles move onto the nesting grounds, their heavy weight compresses the thoracic region making terrestrial breathing laborious and difficult. During phases of nesting, the turtles undergo brief bursts of strenuous and exhaustive exercise which usually lasts less than one minute followed by a brief recovery period which is less than the exercise phase. Reptiles in general, particularly turtles, are intermittent breathers and after bursts of exercise, they appear to develop hypoxia, hypercapnia and acidemia, which are characteristic of anaerobic metabolism. The data reveals that catecholamine levels remain stable in both species during phases of nesting and may play an important role in combating stress as well as mobilizing energy reserves. The high plasma lactate and CO2 levels in olive and hawksbill turtles may signify anaerobic metabolism during exercise. Glucose levels remain unchanged throughout nesting in both species. There was no significant difference in the lactate and glucose values in the two species. The physiological and the behavioral adjustments in this study showed remarkable similarities in the two species and may be an important factor in the reproductive strategy for species survival.